Factorise p³(q-r)³+q³(r-p)³+r³(p-q)³

Asked by jayrbutte1415 | 12th Sep, 2019, 09:38: PM

Expert Answer:

 
p³(q-r)³+q³(r-p)³+r³(p-q)³ = [p(q - r)]3 + [q(r - p)]3 + [r(p - q)]3 
   
If (a  + b + c) = 0, then a3 + b3 + c3 = 3abc

Here q(r - p) + p(q - r) + r(p - q) = 0
 
p³(q-r)³+q³(r-p)³+r³(p-q)³  = 3[p(q - r) × q(r - p) × r(p - q)]
                                              

Answered by Yasmeen Khan | 13th Sep, 2019, 02:37: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.